Role of Melatonin in Down-regulation of Receptor Activator of Nuclear Factor kappa-B Ligand : Osteoprotegerin Ratio in Rat - Bone-Marrow Mesenchymal Stem Cells - Adya Pramusita; Gondo Mastutik; Suhartono Taat Putra (Journal of Krishna Institute of Medical Sciences University, 2018)
Background: Recent studies have reported that melatonin inhibits bone resorption through the regulation of Receptor Activator of Nuclear Factor Kappa-B Ligand (RANΚL): Osteoprotegerin (OPG) ratio in osteoblast. However, the role of melatonin in osteoblast derived from MSCs is unclear. Aim and Objectives: To determine the down-regulation of RANΚL:OPG ratio by melatonin supplementation in osteoblast culture in osteogenic medium derived from rat Bone-Marrow Mesenchymal Stem Cells (BMMSCs). Material and Methods: This research was an experimental research conducted in a laboratory in vitro making use of rat BM-MSCs in osteogenic medium with or without melatonin for a duration of 21 days. Characteristics of MSCs were explored with the use of immunocytochemistry staining (CD45 and CD105). Results: After 15 days, mineralisation assay was carried out by means of Alizarin Red staining and at 21 days the RANΚL and OPG levels were assessed with the use of sandwich ELISA. Conclusion: 150 nM or higher concentrations of melatonin could reduce RANΚL levels; the supplementation of melatonin had no influence on OPG levels, and melatonin could reduce the RANΚL:OPG ratio. The results of this study summarise that melatonin could reduce the RANΚL:OPG ratio in the osteoblast culture originated from rat BM-MSCs.